Hepatoprotective properties for Salvia cryptantha extract on carbon tetrachloride-induced liver injury - Yalcin, Alper; Yumrutas, Onder; Kuloglu, Tuncay; Elibol, Ebru; Parlar, Ali; Yilmaz, Ismet; Aydin, Suleyman (C M B Assoc, 2017)
The present study was designed to determine the possible hepatoprotective effects of Salvia cryptantha (black weed) plant extract against carbon tetrachloride (CCl4)-induced hepatic injury in rats. Animals were grouped as follows: control group (Group I), CCl4 group (Group II), olive oil group (Group III), CCl4 + S. cryphantha 200 mg/kg group (Group IV), and CCl4 + S. cryptantha 400 mg/kg group (Group V). Rats were injected intraperitoneally with CCl4 diluted in olive oil (50% v/v) at a dose of 1ml/kg body weight. Bax and Caspase3 were determined by immunohistochemical staining, while apoptotic index was evaluated using TUNEL assay. Total mRNA was isolated from liver tissues, and the levels of BCL2, Caspase3, SOD, CAT, and glutathione peroxidase (GPx) were determined by using PCR, while MDA level were determined using a colorimetric assay. The antioxidant and anti-apoptotic gene transcripts were decreased in all of the control and treatment groups, while Caspase3 levels were not statistically different. The S. cryptantha plant extract treatment was also found to improve SOD, GPx, and catalase levels, while reducing the serum levels of MDA. The extract of S. cryptantha supplementation had a protective effect against CCl4-induced liver damage. S. cryptantha extract as a supplement may be useful as a hepato-protective agent to combat the toxic effects caused by CCl4 and other chemicals.
Keywords: Carbon tetrachloride; TUNEL; Caspase3; BCL2; Liver injury; Salvia cryptantha